Comprehending the mandate and interactions of land tenure reform in Finnmark, Norway - Broderstad, Else Grete; Josefsen, Eva (Routeledge, 2020)
The land management arrangement – the Finnmark Estate (FeFo) established in Finnmark County - the northernmost county of Norway, is built on indigenous right claims, which implies that particular values, norms and principles are constitutive for and underpin FeFo as an institution. Still, the involved actors - FeFo and the two appointing bodies of the FeFo board - the Sami Parliament and the Finnmark County Council - have not developed a joint understanding of how to address these principles in order to strengthen the focus of FeFo governance. Based on earlier data compiled from investigations about FeFo and the two appointing bodies of the FeFo board, we focus on the relationship between the three institutions in order to explain challenges of cooperation between the three parties concerning the management of land and recourses by FeFo, and how they seek to minimize conflict and contribute to governability. Drawing on the concept of interactive governance, we analyse this governing system in terms of orders of governance by looking into whether the parties have deliberated and developed a set of meta-governance principles that can help in making hard substantive governance choices easier. We will discuss the challenges that may arise between two political bodies, one with a territorial defined mandate and the other with a mandate to secure Sami rights, and a governance and management body with a mandate to cooperate in a situation of high-level conflict.